Analisis Kelayakan Usaha Pemindangan Ikan di UD. Samudra Pasai Desa Sumberanyar Kabupaten Situbondo - Mardiyah, Ulfatul; Jannah, Wildatul; Sawiya, Sawiya; Ningsih, Ika Junia (Fakultas Pertanian, Universitas Timor, 2024)
Pindang fish is a type of traditional processing that functions to extend the relatively short shelf life of fish. Fish farming has the potential to increase national fish consumption and can also improve the community's economy, especially in Sumberanyar Village, Situbondo Regency. Thus, it is necessary to carry out an income analysis to determine whether the business activity is feasible or not. The aim of this research is to determine the revenue value, total costs, profits, and feasibility of fish farming businesses based on the R/C ratio and payback period. The sampling method used in this research is the purposive sampling method. Data collection methods include observation, interviews, literature study, and documentation. Respondents in this research were fish entrepreneurs at UD. Samudra Pasai, Sumberanyar Village, Situbondo Regency. The results of the financial analysis show that the average income is 66,436.000/month, and the average total costs incurred are 55.015.248/month, so the average profit is The average obtained was 11.420.752. Based on the business feasibility analysis, it is known that the R/C ratio is 1.2 and the payback period is 5,7 years. These results indicate that the fish farming business is feasible but requires business development to increase profits so that the payback period is <5 years.